Correction: Enhancement in RNase H activity of a DNA/RNA hybrid duplex using artificial cationic oligopeptides. Issue 81 (28th September 2018) - Hara, Rintaro Iwata; Maeda, Yusuke; Fujimaki, Haruna; Wada, Takeshi
Abstract : Correction for 'Enhancement in RNase H activity of a DNA/RNA hybrid duplex using artificial cationic oligopeptides' by Rintaro Iwata Hara et al., Chem. Commun., 2018, 54, 8526–8529.